Practical guide to implement surveys on ICT use in primary and secondary schools - Martínez, Ana Laura; Ramos Jaimes, Laura Juliana (Comitê de Gestão da Internet no Brasil; Instituto de Estadística de la UNESCO (UIS), 2020)
97 p.